Microbial Community Structure and Metabolic Potential Shape Soil-Mediated Resistance Against Fruit Flesh Spongy Tissue Disorder of Peach - Weifeng Chen; Dan Tang; Jia Huang; Yu Yang; Liangbo Zhang (Agronomy, 2025)
Peach fruit flesh spongy tissue disorder causes dry, porous, and brown areas in the flesh, severely compromising fruit quality and market value. While soil properties and calcium nutrition have been linked to the disorder, the role of rhizosphere microbial communities in disorder resistance remains unclear. This study investigated both the physicochemical properties and the root-associated microbiomes of disordered (CK) and healthy (TT) peach orchards to explore microbial mechanisms underlying disorder suppression. TT soils exhibited higher pH, greater organic matter, increased exchangeable calcium, and more balanced trace elements compared to CK. Microbial analysis revealed significantly higher diversity and enrichment of beneficial taxa in TT associated with plant growth and disorder resistance. Functional gene prediction showed TT was enriched in siderophore production, auxin biosynthesis, phosphate solubilization, and acetoin–butanediol synthesis pathways. Co-occurrence network analysis demonstrated that TT harbored a more complex and cooperative microbial community structure, with 274 nodes and 6013 links. Metagenomic binning recovered high-quality MAGs encoding diverse resistance and growth-promoting traits, emphasizing the ecological roles of Gemmatimonadaceae, Reyranella, Nitrospira, Bacillus megaterium, and Bryobacteraceae. These findings highlight the combined importance of soil chemistry and microbiome structure in disorder suppression and provide a foundation for microbiome-informed soil management to enhance fruit quality and promote sustainable orchard practices.